The effect of taurine supplementation on markers of muscle damage and muscle pain in an athletic population: A systematic review and meta-analysis of randomized controlled trials assessed using the grading of recommendations, assessment, development, and evaluation approach - Elaheh Dehghani; Fatemeh Naeini; Sakineh Shab Bidar; Mohammad Beba; Erfan Mortezapour; Ruhollah Nourian; Khashayar Danandeh; Zahra Gohari Dezfuli; Kurosh Djafarian (Heliyon)
Background: Moderate to intense physical activity is vital for health but may lead to exercise-induced muscle damage (EIMD) and muscle pain. Taurine supplementation (TS) is used to aid post-exercise recovery. This systematic review and meta-analysis examines the effects of TS on EIMD and muscle pain in athletes. Methods: PubMed, Scopus, and Web of Science were systematically searched for randomized controlled trials (RCTs) on TS in athletic populations until March 2025. Also, studies with adult participants (≥18 years), a placebo or control group, and at least one biomarker (creatine kinase (CK), lactate dehydrogenase (LDH), or visual analog scale (VAS) for pain) were included. A fixed or random-effects model was used based on heterogeneity (I2), and Egger's test was used to assess publication bias. In addition, the grading of recommendations assessment, development, and evaluation (GRADE) approach evaluated evidence certainty. The included studies were conducted in clinical exercise laboratories, sports science research centers, and university training facilities. Results: Seven RCTs (2009–2017) with 165 participants were included. TS significantly reduced post-exercise CK levels (weighted mean difference [WMD] = −7.91 international units per liter [IU/L], 95 % confidence interval [CI]: −122.21 to 138.04, I2 = 95.9 %) and CK levels after 24 h (WMD = −78.28 IU/L, 95 % CI: −211.55 to 54.99, I2 = 81.5 %). LDH levels from post-exercise to 48 h also decreased, as well as VAS pain scores after 96 h. However, no significant changes were found for LDH beyond 48 h or earlier VAS pain scores. Egger's test showed minimal publication bias, except for LDH at post-exercise to 48 h (p = 0.028) and beyond 48 h (p = 0.008). Evidence certainty was low due to high heterogeneity across the included studies. Conclusion: TS may support post-exercise muscle recovery by reducing CK and LDH levels, but its effect on muscle pain remains unclear. While it shows potential as a recovery aid for athletes, further research is needed to optimize dosing and practical applications in sports performance and rehabilitation.